2002
DOI: 10.1192/apt.8.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Use of medicines in nursing homes for older people

Abstract: The National Health Service (NHS) spent £10 billion (40%) of its total budget on people aged 65 and over in 1998/1999. The profile of the health and social care of older people has been raised recently by the publication of the National Service Framework (NSF) for Older People (Department of Health, 2001). The NSF contains standards that older people can expect when they receive health and social care (Box 1). The document also discusses in detail medication management issues in older people. Its two aims in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…Research has found that residents living in residential aged care homes (RACHs) were prescribed significantly more medications than those living independently [2]. International studies found that residents in…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that residents living in residential aged care homes (RACHs) were prescribed significantly more medications than those living independently [2]. International studies found that residents in…”
Section: Introductionmentioning
confidence: 99%
“…The need to improve safety in the management of medication in care homes has been identified by several authors (Furniss 2002, Simonson and Feinberg 2005, Snowdon et al 2006. In England, over 18,000 homes currently provide care for more than 453,000 residents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Banning (2004) confirms this arguing that older people desist from adhering to care plans for the same practical, economical, logistical, social and belief reasons as the rest of the us. It is interesting that much polypharmacy among older people has been found to exist in nursing homes where paternalistic models of medicine management are still in place and residents were not involved in the review or evaluation of their treatment profiles (Furniss, 2002).…”
Section: Concordance and Older Peoplementioning
confidence: 99%